PERSIDANGAN PERKARA PIDANA DI PENGADILAN SECARA ELEKTRONIK DALAM PEMBAHARUAN HUKUM ACARA PIDANA - Maria Palayukan (2022)
This research was conducted for the implementation of the trial of criminal cases in courts that have been carried out electronically. So far, the implementation of electronic criminal case trials has been running for approximately 2 years since the pandemic hit Indonesia. Through PERMA No. 4/2020 which is the legal umbrella for electronic criminal case trials, it is still felt that it does not regulate the trial process and raises various questions such as the validity of the defendant's presence at the trial which is conducted electronically, the problem of transferring case files, even the validity of evidence and evidence. As the goal of the Supreme Court in creating a technology-based integrated criminal justice system, this electronic trial of criminal cases is a breakthrough. PERMA No. 4/2020 each is considered unable to become a legal umbrella for criminal case trials electronically. Based on this, the problem in this paper is in the form of what are the obstacles to the implementation of electronic criminal case trials and how to prove criminal cases in electronic trials in the future. This writing uses a normative juridical research method with a statute approach and a comparative approach. Completion of obstacles in the form of validity of tools and evidence as well as networks in the form of changes to PERMA No. 4/2020, improving facilities and infrastructures especially outside Java Island and implementating e-Berpadu.